USE OF DIFFERENT TECHNIQUES OF VISUALIZATIONS IN THE TRAINING OF ENGINEERING SPECIALISTS: NEEDS VERSUS APPROACHES - Veide, Zoja; Strozheva, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The quality of engineering education is closely related to the development of spatial skills of students and the ability to create and read the drawings. Visualization improves the efficiency of the information; as for visualization of geometric tasks of graphical subjects, it helps students faster comprehend complex spatial problems and solve the given exercises.The given article describes the study of the methodology of teaching graphical subjects from the point of view of methods of representations of education materials, the degree of inspiration and engagement of students in learning activities. The research was conducted in Latvia, Lithuania, Spain, Germany and Poland within the project "Contemporary Approach to the Development of Spatial Comprehension through Augmented Reality Content" (SPACAR).